The influence of music in the development of phonetics, phonology and phonological awareness in 3-year-olds with typical development and 3- to 6-year-olds with speech or language disorder - Vidal, Maria Manuel Duarte Guimarães (2020)
The relation between music and language has been intensively studied in recent years. Research has revealed that both domains engage similar processing mechanisms, including auditory processing and higher cognitive functions, and recruite partially overlapping brain structures. Furthemore, different authors have shown that linguistic functions can be positively influenced by music training above 4 years old. Music has also been shown to be associated with the promotion of linguistics skills in children with specific pathologies related to language, such as dyslexia, in 7- to 10-year-olds. In this thesis, we conducted four studies on the effect of music training on different aspects of language development. We studied this influence on phonological awareness in children with typical development and speech or language disorder (Studies 1 and 2) and on phonetic and phonological development in the same populations (Studies 3 and 4). In this randomized control study, with a test-training-retest methodology, 49 typically developing children, aged between 3 and 4, were assessed with a phonological awareness test (Study 1) and a phonetic and phonological test (Study 3). These tests were applied before and after a school year with weekly Music Classes (experimental group) or Visual Arts Classes (control group) in kindergarten. Two additional studies with the same methodology were conducted with 16 atypically developing children, aged between 3 and 6. This group included children with phonologically based Speech Sound Disorder (SSD) and / or Developmental Language Disorder (DLD). The goal of investigating this topic in this group of atypical children was to understand music relation with phonological awareness development (Study 2) and phonetic and phonological development (Study 4), and this at stages earlier than those where the beneficial effect of music in language-related skills has already been found. When comparing pre- and post-assessment and irrespective of type of lessons’ exposure (music or visual arts), results always showed significant differences in each group, as expected due to general developmental reasons. In Study 1, Music Classes’ students outperformed the control group, showing significantly larger differences between the beginning and the end of the lessosns period, indicating that music lessons have influenced phonological awareness, and pointing to a causal relation between music training and phonological awareness as soon as 3 years of age. In Studies 2, 3 and 4 no significant differences were found between groups in the post-assessment moment. This fact may suggest the need of more intensive music training or, in what concerns atypically developing children, a specific music curriculum designed to bridge their linguistic rhythm (and possibly pitch) processing deficits. Globally, this thesis supports the hypothesis that music training may promote language abilities, in particular phonological awareness, in 3-year-olds with typical development, that is prior to the ages that have been previously studied.